Tuberculosis prediction system using artificial neural network / Farisah Mamat @ Mohammad - Mamat @ Mohammad, Farisah (2012)
Tuberculosis could be predicted using the Artificial Neural Network. This system will reduce the time and cost to predict the tuberculosis disease. ANN will use past datas to run and compare with the new data that will predict whether the individual contracted tuberculosis disease or not. There are a lot of techniques that can be used to make predictions, but the technique which is suitable to be used to make this prediction is neural network system This is because the neural network has two other types of techniques which can be used as feed forward and backward techniques. Back-propagation is one of the feed forward techniques that can be used when we know what the output that will carry out after the information (data) are keyed in.